2020
DOI: 10.1177/1708538120949658
|View full text |Cite
|
Sign up to set email alerts
|

Prediction, pattern recognition and modelling of complications post-endovascular infra renal aneurysm repair by artificial intelligence

Abstract: Objectives The study evaluates the plausibility and applicability of prediction, pattern recognition and modelling of complications post-endovascular aneurysm repair (EVAR) by artificial intelligence for more accurate surveillance in practice. Methods A single-centre prospective data collection on ( n = 250) EVAR cases with n = 26 preoperative attributes (factors) on endpoint of endoleak (types I–VI), occlusion, migration and mortality over a 13-year period was conducted. In addition to the traditional statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Our model features end-to-end training which is a methodology that uses images as the only input without any human or software directed measurements or calculations, in which features were automatically learned and selected from the downloaded data. Such a training pipeline has been widely adopted in 10 other areas and successfully implemented in other applications of AI. 14 The positive results attained with our model in this study suggests that it can be useful in other areas of vascular surgery as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our model features end-to-end training which is a methodology that uses images as the only input without any human or software directed measurements or calculations, in which features were automatically learned and selected from the downloaded data. Such a training pipeline has been widely adopted in 10 other areas and successfully implemented in other applications of AI. 14 The positive results attained with our model in this study suggests that it can be useful in other areas of vascular surgery as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our work has demonstrated that radiomics datasets can capture the level of complexity of the phenomenon. AI has been also used to predict reintervention and mortality after EVAR without providing data on the effects of T2EL (17) and artificial neural networks were able to accurately predict the appearance of endoleak or occlusion (18). Along the same lines, Ding et al (19) utilized texture analysis, a limited version of radiomics, to predict sac expansion after EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…Korzadeh et al applied AI to predict not only the presence, but also the severity of EL (I-III). The model was fed with 26 non-imaging clinical attributes (e.g., biometrics, demographics, blood values) recorded preoperatively and achieved an overall accuracy of more than 86% (125). The authors notice that the model may well be further enhanced with imaging data, highlighting the adaptability of AI in different and diverse datasets and its high potential to provide even more powerful tools for the clinical management of AAA in the future.…”
Section: Abdominal Aortic Aneurysmmentioning
confidence: 99%